Human Cathepsin V Protease Participates in Production of Enkephalin and NPY Neuropeptide Neurotransmitters - Funkelstein, Lydiane (American Society for Biochemistry and Molecular Biology, 2012)
Proteases are required for processing precursors into active neuropeptides that function as neurotransmitters for cell-cell communication. This study demonstrates the novel function of human cathepsin V protease for producing the neuropeptides enkephalin and neuropeptide Y (NPY). Cathepsin V is a human-specific cysteine protease gene. Findings here show that expression of cathepsin V in neuroendocrine PC12 cells and human neuronal SK-N-MC cells results in production of (Met)enkephalin from proenkephalin. Gene silencing of cathepsin V by siRNA in human SK-N-MC cells results in reduction of (Met)enkephalin by more than 80%, illustrating the prominent role of cathepsin V for neuropeptide production. In vitro processing of proenkephalin by cathepsin V occurs at dibasic residue sites to generate enkephalin-containing peptides and an ∼24-kDa intermediate present in human brain. Cathepsin V is present in human brain cortex and hippocampus where enkephalin and NPY are produced and is present in purified human neuropeptide secretory vesicles. Colocalization of cathepsin V with enkephalin and NPY in secretory vesicles of human neuroblastoma cells was illustrated by confocal microscopy. Furthermore, expression of cathepsin V with proNPY results in NPY production. These findings indicate the unique function of human cathepsin V for producing enkephalin and NPY neuropeptides required for neurotransmission in health and neurological diseases.